O trabalho social na política de habitação: estudo sobre as intervenções na Favela de Heliópolis/SP (2005-2012) - Freitas, Maria Joelma Libório de Lima (2021)
This master's thesis aims to study the social work in Housing Policy considering the interventions carried out in the favela of Heliópolis/SP from 2005 to 2012, aiming to understand its limits, its main marks and contributions to the lives of the benefited families. A brief contextualization is presented on the urbanization process of cities and their spaces that, in view of the advance of capitalism, led the poor population to occupy slums favelas and precarious settlements, with precarious conditions of infrastructure and public services, and the policies and programs adopted to attend these situations lack of access to decent housing. Approaches to Housing Policy and the insertion of social work in Brazil and São Paulo/SP, in addition to the rescue of the main housing interventions in public administrations of this city, from the mid-1970s to 2012, contemplating the formation period from the Favela Heliópolis. Approaches the history of Heliópolis about collective struggles by the population to stay on the land and for better housing and infrastructure conditions, as well as the social work developed in the mentioned periods. The adopted methodology is inserted in a critical perspective, with a qualitative nature, including bibliographical, documentary and empirical research. Interviews were carried out with professionals who worked during this period, residents´ benefit with housing units and local leaders, to contemplate the different perceptions of the people involved. The study presents as main results the perception of the interviewed about interventions and social work. From the perspective of professionals, residents and leaders, public interventions and social work guaranteed the beneficiary population improvement in the population´s living conditions and new housing, however part of the families showed dissatisfaction with the your housing, in its physical and structural aspects, in relation to the design of the floor plan of the condominiums and apartments, and with the size of the units. There was an intensification of social work carried out simultaneously in Heliopolis, due to large investments and works; it was noticed that the location and the conditions of the houses interfere in the acceptance of the families to the project. The results showed that the social work developed represented an important differential in the interventions, despite showing numerous difficulties and contradictions experienced in the context of implementation of the Housing Policy. Heliópolis underwent public interventions in all municipal administrations, however, these failed to resolve, in its entirety, the issue of urbanization, urban infrastructure, housing provision and land regularization